Evaluation of IL- 2 and IFN γ levels in recovered COVID 19 Patients and Vaccinated Participants, Comparative Study in AL-Diwaniyah, Iraq - Kdhem, Esraa Jawad; Ghaidaa Jihadi (South Eastern European Journal of Public Health, 2024)
The coronavirus disease 2019 (COVID-19), is a highly contagious transmittable disease caused by a recently discovered coronavirus, pathogenic SARS-CoV-2. Coronavirus is considered one of the diseases arisen recently, Thus, The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has consequently resulted in a notable rate of morbidity and mortality. There are hopes that vaccination generated immunity or infection generated immunity or from herd achieved through both natural SARS-CoV-2 infection and vaccination, can control it. So, this study aimed to evaluated of IL- 2 and IFN γ levels in COVID-19 recovered patients, vaccination and hybrid (infected and vaccinated) for three months after infection or vaccination. This study was conducted on 165 COVID-19 Iraqi recovered patients, hybrid and vaccinated (males and females) with age ranged between 15-75 years, and 85 matched healthy control group. The nasopharyngeal swabs was used to confirm recovery via Real-Time Polymerase Chain Reaction (RT-PCR) technique. Blood samples collected for ELISA (enzyme-linked immunosorbent assay). There was significant difference in mean age (p = 0.007) among groups and the highest mean age was for recovered group (37.95 ±14.81) years followed by hybrid group(35.80 ±14.96)years and vaccinated group (33.93 ±16.06)years , the least mean age was for control group (29.84 ±12.20) years. While, there was no significant difference in the frequency distribution of subjects according to sex among study groups (p = 0.899). In addition there was significant increase (P< 0.001) 0f IL-2 level in COVID-19 recovered patients that taken vaccines group (210.37 ±36.51 pg/mL) followed by recovered patients (181.52 ±24.54 pg/mL) and vaccinated persons (178.81 ±17.50 pg/mL)as compared to healthy control group(148.91 ±7.14 pg/mL). There was significant difference in mean of IFN-gamma level (p < 0.001) and the level was highest in infected and vaccinated group(213.73 ±77.46 pg/mL) followed by vaccinated (188.99 ±33.31 pg/mL)and recovered groups (186.99 ± 46.11 pg/mL) then lastly by control group(145.06 ±5.34 pg/mL).Moreover, there was a strong positive correlation between IL-2 and IFN-γ (r = 0.534),( P<0.001) in COVID-19 recovered group .